Characterization Of Leptospiral Isolates Obtained From Selected Cattle Farms In Malaysia - Bejo, Siti Khairani (1997)

(untitled)
Leptospirosis is an infectious disease of animals and man in many parts of the world. It is caused by Leptospira and has been classified as an important zoonotic disease. A serological survey in four selected dairy cattle farms in Malaysia revealed 36% (114/318) of the animals examined had leptospiral infection. Antibodies to serovar hardjo was the main (19%) serovar detected . A bacteriological survey revealed only 1.2 % (3/244) of the cattle examined had leptospiral infection. Two isolates obtained have been identified as L. hardjo and another one as L. pomona. Bacteriological study did not come across any multiple leptospiral serovar infection in the cattle farms studied. The serological prevalence of serovar pomona infection was very low. However, one isolate that has been identified as serovar pomona was isolated from cattle in Sungai Siput Farm in this study. This finding suggested that cattle in this farm might be maintaining the serovar pomona infection.